Pengaruh Kompetisi dan Kooperasi Melalui Koopetisi Terhadap Kinerja Perusahaan(Studi Kasus Pada UMKM Retail Komputer di SCC, Plaza Simpang Lima Semarang) - Njoo, Conny Elysia Lazaroni; Sentot Suciarto Athanasius (Universitas Katolik Soegijapranata, Semarang, 2019)
This research examines the effect of competition and cooperation toward performance through coopetition of computer retail SMEs. This research used path analysis toward 31 SMEs computer retail by purposive sampling. Data collected by questionnaires. The research result showed that competition did not influence toward cooperation and performane, coopetition showed positive effect toward coopetition and business performance. Competition and cooperation through coopetition did not affect business performance.